1977
DOI: 10.1037/0021-843x.86.6.609
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the expression of depressive responses on the Beck Depression Inventory.

Abstract: Although epidenniological data have documented sex differences in depression, the nature and origins of the differences are unclear. Depression in a large sample of young, unmarried college students was measured and described by the Beck Depression Inventory. No sex differences were found in the degree of depression experienced by these students, and yet, discriminant function analysis of the responses of the most depressed scorers yielded a significant and interpretable sex difference in the patterns of sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
110
1
6

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 9 publications
18
110
1
6
Order By: Relevance
“…We also expected the MDS to correlate strongly with the somatic symptoms assessed by the traditional depression scales and weakly with the emotion-focused symptoms. Men who adhere to hegemonic masculine norms tend to endorse somatic symptoms of depression and tend to avoid endorsing emotion related symptoms (e.g., crying frequently) (Hammen & Padesky, 1977;Salokangas, Pacriev, Sohlman, & Lehtinen, 2002). To further assess the scale's convergent validity, it was hypothesized that the MDS would correlate strongly with the Gotland Scale of Male Depression, because both of these scales purport to measure the same underlying construct.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We also expected the MDS to correlate strongly with the somatic symptoms assessed by the traditional depression scales and weakly with the emotion-focused symptoms. Men who adhere to hegemonic masculine norms tend to endorse somatic symptoms of depression and tend to avoid endorsing emotion related symptoms (e.g., crying frequently) (Hammen & Padesky, 1977;Salokangas, Pacriev, Sohlman, & Lehtinen, 2002). To further assess the scale's convergent validity, it was hypothesized that the MDS would correlate strongly with the Gotland Scale of Male Depression, because both of these scales purport to measure the same underlying construct.…”
Section: The Current Studymentioning
confidence: 99%
“…For example, men diagnosed with depression are more likely to have comorbid alcohol abuse problems (Angst et al, 2002;Roeloffs, Funk, Unutzer, Tang, & Wells, 2001). Men are also more likely than women to report engaging in activity to avoid thinking about their depression and to report somatic complaints, concerns regarding work success, inability to make decisions, and general social withdrawal (Hammen & Padesky, 1977;Kessing, 2006;Kleinke, Staneski, & Mason, 1982;Kornstein et al, 2000;Padesky & Hammen, 1981;Vredenburg, Krames, & Flett, 1986;Winkler et al, 2004). On the other hand, men are less likely than women to report crying (Hammen & Padesky, 1977;Kleinke et al, 1982;Salokangas, Pacriev, Sohlman, & Lehtinen, 2002).…”
mentioning
confidence: 99%
“…First, although research shows that the rate of depression is typically found to be twice as high in women as compared to men (Culbertson, 1997;Nolen-Hoeksema, 1990;Weissman & Olfson, 1995), it is important to note that gender differences in the rate of depression are not typically found in college samples (e.g., Hammen & Padesky, 1977;Stangler & Printz, 1980). Nonetheless, research using college samples can be useful in isolating gender differences in the types of factors that contribute to variance in dysphoria within these samples.…”
Section: Discussionmentioning
confidence: 99%
“…Il faut cependant noter quelques exceptions en Australie (Parker, 1979), au Missouri et au Maryland (Comstock et Helsing, 1976). Les différences de sexe sont également absentes chez une population de collégiens américains, donc plus jeune et à très grande majorité céliba-taire (Hammen et Padesky, 1977). L'écart observé pour les troubles mineurs disparaît ordinairement quand il s'agit de troubles majeurs.…”
Section: Les Femmes En Moins Bonne Santé Mentale ?unclassified
“…A notre avis cependant, le facteur de sélection risque peu de jouer dans les pays du tiers monde où la femme a peu de responsabilité personnelle dans la décision d'immigrer. Nous croyons plutôt que là où les rôles sont égale-ment valorisés, qu'ils soient similaires comme dans les universités ou très différenciés comme dans certaines sociétés traditionnelles, les écarts entre les taux de dépression s'amenuisent (Hammen et Padesky, 1977).…”
Section: Les Femmes En Moins Bonne Santé Mentale ?unclassified